Fireborne - Munda, Rosaria (New York : Putnam, G.P. Putnam's Sons, 2019)
Annie and Lee were just children when a brutal revolution changed their world. Now they are both rising stars in the new regime. Annie's lowborn family was executed by dragonfire, while Lee's aristocratic family was murdered by revolutionaries. Growing up in the same orphanage forged their friendship, and seven years of training have made them rivals for the top position in the dragonriding fleet. But when survivors from the old regime surface, Lee must choose to kill the only family he has left or to betray everything he's come to believe in. And Annie must decide whether to protect the boy she loves, or step up to be the champion her city needs--Adapted from jacket.
MSBA nominee 2020-2021.
Keywords: Dragons -- Juvenile fiction; Orphans -- Juvenile fiction; Government, Resistance to -- Juvenile fiction; Military education -- Juvenile fiction; Young adult fiction; Fantasy fiction